Анализа корелације серумског ФГЛП1, УАЦР и ризика од срчане инсуфицијенције код пацијената са дијабетесом типа 2: Серум ФГЛП1, УАЦР и ризик од срчаног застоја код Т2Д - Xia, Lianheng; Guo, Yingshuo; Wang, Jiaxin; Wang, Tingxuan; Xu, Chunhui; Song, Meiyu; Du, Chang; Wang, Qingjie; Gao, Jie (Journal of Medical Biochemistry, 2026)
Objective To explore the correlations between serum FGLP1 (Fibrinogen-like protein 1 C-terminal peptide) levels, the urine albumin-to-creatinine ratio (UACR) and left ventricular diastolic dysfunction (LVDD) in elderly patients with type 2 diabetes mellitus (T2DM).Methods From August 2023 to August 2025, 256 elderly patients with T2DM who were admitted to our hospital were selected as the case group, and 120 healthy individuals who underwent physical examinations were selected as the control group. In accordance with the diagnostic criteria for LVDD, T2DM patients were divided into a disorder group (n=70) and a nondisorder group (n=186), and single-factor analysis, multivariate logistic regression analysis, and Spearman correlation analysis were performed to explore the correlation between serum FGLP1 levels, UACRs and LVDD in T2DM patients, and receiver operating characteristic curves were used to evaluate the ability of serum FGLP1 levels and urine UACR to predict LVDD.Results The serum FGLP1 concentration and urine UACR were higher in the case group than in the healthy group (P
Keywords: Дијабетес типа 2; Дијастолна дисфункција левог срчаног комора; Фибриноген-слични протеин 1 пептид са C-терминалом; Однос албумина у урину и креатинина